2019
DOI: 10.3389/fbioe.2019.00292
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Conditioned Mesenchymal Stem Cell-Derived Extracellular Vesicles Induce Increased Vascular Tube Formation in vitro

Abstract: Mesenchymal stem/stromal cells (MSCs) display a variety of therapeutically relevant effects, such as the induction of angiogenesis, particularly under hypoxic conditions. It is generally recognized that MSCs exert their effects by secretion of paracrine factors and by stimulation of host cells. Furthermore, there is increasing evidence that some therapeutically relevant effects of MSCs are mediated by MSC-derived extracellular vesicles (EVs). Since our current knowledge on MSC-derived EVs released under hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 72 publications
4
130
1
1
Order By: Relevance
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…EVs are produced constitutively or upon activation, due to inflammation, hypoxia, oxidative stress, shear stress, senescence, cell death, exposure to bacterial endo/exotoxins, uremia, etc. [10][11][12][13][14][15]. The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Furthermore, the biogenesis and secretion of exosomes released from MSC also depend on external stimuli. For instance, MSC undergoing hypoxia or inflammation could influence the biomolecule packaging process into exosomes and affect their functional properties, such as the hypoxia‐conditioned MSC‐derived exosomes exerting more angiogenic activity than normoxic exosomes 12 . The Wnt and mTOR pathways are considered as “master regulators” involved in the enhancement of self‐renewal in MSC by increasing β‐catenin expression, and are also required for exosome secretion 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…Co-transplantation of exosomes with a fat graft resulted in increased expression of EGF, fibroblast growth factor, angiopoietin-1, and angiopoietin receptor (Tie-1) proteins [110]. It was observed that exosomes from hypoxia-primed MSCs versus MSCs cultured under normoxic conditions were more easily taken up by HUVECs; the uptaken exosomes promoted vascular endothelial growth factor (VEGF) expression and protein kinase A signaling pathway activation, which resulted in improved angiogenesis by HUVECs [111,112]. Exosomes from hypoxia-primed MSCs have also been shown to promote myocardial repair.…”
Section: Pre-conditioning Of Mscs With Hypoxiamentioning
confidence: 99%